Pengaruh Pendapatan Terhadap Tingkat Kesejahteraan Petambak Garam Di Desa Arungkeke Kabupaten Jeneponto - Nur Aisyah Qadri Saiful (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Prosperity is something that is hoped for by all levels of society because community or household inequality can be interpreted as a poor community or household. One important factor of welfare is income. The aim to be achieved in this research is to determine whether income has a positive effect on the level of welfare of salt farmer households in Arungkeke village, Arungkeke subdistrict, Jeneponto regency. This research design method is a survey method using a qualitative and quantitative approach where the unit studied is salt farmers. The influence of income on the level of welfare has a positive effect. To achieve prosperity, one of the factors is income.